Problematika dan Tantangan Pembelajaran Bahasa Arab di Ma’had Al-Jami’ah UIN Bandung : Penelitian - Sofia Laila Rahmah; Irfan Muhammad Ihsanuddin; Isop Syafe’i (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Arabic language learning at Ma'had Al-Jami'ah plays a strategic role in supporting Islamic studies for students at Islamic universities, but still faces various problems that affect its effectiveness. This study aims to identify and analyze the problems and challenges of Arabic language learning at Ma'had Al-Jami'ah UIN Bandung using a descriptive qualitative approach. The results show that the problems stem from two main aspects: educators and students. From the educators' perspective, obstacles include suboptimal learning readiness, insufficiently varied methods, and inconsistent formation of the language environment (bi'ah lughawiyah). From the students' perspective, problems include differences in background and initial Arabic language abilities, low learning motivation, and limited individual mentoring. These findings indicate that the problems of Arabic language learning are multidimensional and require comprehensive handling through strengthening communicative methods, consistent language environment management, and adaptive mentoring strategies.